(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2011)
Present work is to carry out an analytical method development and validation of Fluoxetine HCl (FLU) and Olanzapine (OLZ) in bulk drug and pharmaceutical dosage form. The developed method is based upon simultaneous equations (Vierodt’s) method by using UV/Visible spectroscopy. Both drugs come in the categories of anti- depressant and anti-psychotic agent. The developed method can be used for the simultaneous estimation of FLU and OLZ in pharmaceutical dosage form without separating from each other or from the excipients. Primarily the λ max of Fluoxetine HCl (FLU) and Olanzapine (OLZ) was determined as 226 and 258 nm respectively. The suggested method is validated by using ICH validation parameters like accuracy, precession, linearity and LOD and LOQ respectively. Accuracy study showed percentage recovery in the range of 97-102% w/w respectively. Precision studies were carried out for 6 successive absorbance and studied for their percentage relative standard deviation (%RSD) was < 2%, LOD and LOQ was studied and the limit of detection and limit of quantification were found to be was 1-100 µg/ml for Olanzapine and Fluoxetine HCl, the slope of interception Y=0.23x6+0.054 (R2 0.993) and Y=0.222x6-0.014 (R 2 0.995) respectively. Relative standard deviation for Fluoxetine hydrochloride and Olanzapine were 0.4904 and 0.53969, the co-relation coefficient were 0.997 and 0.825 respectively. This procedure was applied successfully for the analysis of FLU and OLZ in bulk drug and Pharmaceutical preparations.